Talîl al-Ahkâm dan Pembaruan Ushul Fikih - Muhammad Nashirudin (Universitas Islam Negeri Jakarta, 2015)
Renewal of Islamic law was necessary to renewal fiqh and ushûl al-fiqh which become the method of determination of Islamic law. Among the classical fiqh issues that can currently be used as the entrance to reform is to perform the renewal talîl al-ahkâm process, namely by making the wisdom and interests as a determinant of the presence and absence of law in a matter.DOI: 10.15408/ajis.v15i1.2844